Stochastic Programming Based on Traveling Salesman Problem with Stochastic Cost - Zhou, Lei; Yang, Xiao Zheng; Li, Qing Chun; Hui, Hong Qi (Applied Mechanics and Materials, 2013)
The research of traveling salesman problem (TSP) is important in logistics distribution. Because many stochastic cost factors affecting logistics distribution in real life, a class of stochastic programming model is considered in TSP in this paper. Through given a class of synthesizing effect functions which synthesis expectation and variance of cost factors, stochastic programming model of TSP with stochastic cost can be converted into a class of crisp programming models. A genetic algorithm based on real coding is used in an illustrative example. It is provided to show the effectiveness of the proposed model and method.